2022
DOI: 10.3390/audiolres12060063
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Syllable Training Improves Phoneme Identification in Older Listeners with and without Hearing Loss

Abstract: Acoustic-phonetic speech training mitigates confusion between consonants and improves phoneme identification in noise. A novel training paradigm addressed two principles of perceptual learning. First, training benefits are often specific to the trained material; therefore, stimulus variability was reduced by training small sets of phonetically similar consonant–vowel–consonant syllables. Second, the training is most efficient at an optimal difficulty level; accordingly, the noise level was adapted to the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Kucuk, Dere and Mujdeci (2022) [139] found a significant decrease in MMN latencies as a result of auditory training. Additionally, Schumann and Ross (2022) [140] found that adaptive syllable training improves phoneme identification in older listeners with and without hearing loss. However, similar pre-test accuracy (80% correct) could only be achieved at lower SNRs in the listeners without hearing loss post-training.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…Kucuk, Dere and Mujdeci (2022) [139] found a significant decrease in MMN latencies as a result of auditory training. Additionally, Schumann and Ross (2022) [140] found that adaptive syllable training improves phoneme identification in older listeners with and without hearing loss. However, similar pre-test accuracy (80% correct) could only be achieved at lower SNRs in the listeners without hearing loss post-training.…”
Section: Section 2: Clinical Implications and Recommendationsmentioning
confidence: 99%